2017
DOI: 10.12973/iji.2017.10112a
|View full text |Cite
|
Sign up to set email alerts
|

The Home Literacy Environments of Turkish Kindergarteners: Does SES Make a Difference?

Abstract: This study investigated the possible differences in the home literacy environments (HLE) among Turkish kindergarteners from three different SES (socio-economic) strata. 341 parents of a total of 341 kindergarteners from 24 kindergarten classrooms in low, middle and high SES neighbourhoods across Ankara completed the Socio-Demographics Form and the Home Literacy Questionnaire (HLQ). Results of MANOVA and the Kruskal-Wallis test revealed significant differences among the three SES levels, with high SES scoring s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 17 publications
(34 reference statements)
3
12
0
6
Order By: Relevance
“…In the present study, it was identified that high correlations existed between HSQ-T scores and the independent variables, while significant but low negative correlations were noted between home quality and the AI-T scores of the children. The effects of the characteristics of the parents and children on family home quality have been studied for many years, and there is evidence that the mother's education level, income, and working status are strong predictors of SES (Ensminger & Fothergill, 2003) and important variables associated with not only the overall home environment (Biedinger, 2011;Goemans, Van Geel, Vedder, & Bradley, 2016;Pessanha & Bairrao, 2003;Richter, & Grieve, 1991) but also the home learning environment of typically developing children (Ergül et al, 2017;Niklas, Chorssen, & Tayler, 2016). It has been emphasized that families with low income and education levels are less likely to provide a stimulating environment and learning experiences for their children due to financial restrictions (Cooper, Crosnoe, Suizzo, & Pituch, 2010;Yeung, Linver, & Brooks-Gunn, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, it was identified that high correlations existed between HSQ-T scores and the independent variables, while significant but low negative correlations were noted between home quality and the AI-T scores of the children. The effects of the characteristics of the parents and children on family home quality have been studied for many years, and there is evidence that the mother's education level, income, and working status are strong predictors of SES (Ensminger & Fothergill, 2003) and important variables associated with not only the overall home environment (Biedinger, 2011;Goemans, Van Geel, Vedder, & Bradley, 2016;Pessanha & Bairrao, 2003;Richter, & Grieve, 1991) but also the home learning environment of typically developing children (Ergül et al, 2017;Niklas, Chorssen, & Tayler, 2016). It has been emphasized that families with low income and education levels are less likely to provide a stimulating environment and learning experiences for their children due to financial restrictions (Cooper, Crosnoe, Suizzo, & Pituch, 2010;Yeung, Linver, & Brooks-Gunn, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A strong relationship was found between the frequency of maternal participation in child activities and home quality. Previous literature frequently emphasizes that the home learning environment, when including parental involvement in the activities of children, is the context in which all children have the opportunity to acquire and practice various skills through meaningful interactions with people, materials, toys and events in the home (Biedinger, 2011;Ergül et al, 2017;Hayes et al, 2018;Iltus, 2006;Niklas & Schneider, 2017). Activities such as read-aloud, playing number games, board and card games, and art/craft activities are accepted as home learning activities when there is parental involvement, as such activities support the development of children by providing various opportunities for communication and interaction with their parents (Farrant & Zubrick, 2013;Melhuis et al, 2008;Senechal, Pagan, Lever, & Quelette, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…"Erken okuryazarlık programlarının etkileri ve bu programlar kullanılarak ev ortamında erken okuryazarlığın desteklenmesi" amaçlarıyla yapılan lisansüstü tez çalışmalarının da sayısal açıdan fazla olduğu bulunmuştur. Bu durum erken okuryazarlık kavramına ilişkin gerek yetişkinlerin bilgi, tutum ve beceri açısından kendilerini geliştirme çabası içerisinde olduklarını göstermek ve gerekse çocukların erken müdahale kapsamında yer verilen ev ortamlarında erken okuryazarlıkla tanışmalarını ve akademik açıdan daha donanımlı bir şekilde ilkokula başlamalarını sağlayarak gelecekteki akademik başarılarını desteklemek açılarından büyük önem taşımaktadır (Ergül, Dolunay Sarıca, Akoğlu & Karaman, 2017;Gül, 2007;Işıkoğlu Erdoğan, 2016;Kınık, Okyay & Aydoğan, 2016).…”
Section: Tartışma Ve Sonuçunclassified